Endometriosis and aspirin: a systematic review - Yang, Yi; Lai, HanHong; Li, ZhengJuan; Zhang, Jun (Frontiers in Endocrinology, 2024)
Endometriosis is delineated as a benign yet steroid-dependent disorder characterized by the ectopic presence of endometrial glandular and stromal cells outside the uterine cavity, affecting estimated 10%-15% of women of reproductive age, 20%-50% of all women with infertility and costing a great economic burden per-patient(1).Endometriosis exerts pervasive influence on multiple facets of female reproductive physiology. Given its characterization as a chronic inflammatory disorder, escalated levels of pro-inflammatory cytokines were unequivocally recognized as wellestablished characteristics of endometriosis, which might attribute to mechanisms like retrograde menstruation, progesterone receptor resistance, and immune dysregulation.Therapeutic utilization of non-steroidal anti-inflammatory drugs (NSAIDs) like aspirin, analgesic agent for reducing pain, inflammation, and fever, could be holding promise in augmenting reproductive outcomes of endometriosis women(2).Therefore, the objective of this comprehensive review is to elucidate the intricate interplay between endometriosis and aspirin, both within the context of infertility and beyond. We meticulously explore potential pharmacological agents targeting endometriosis, which may concurrently optimize the efficacy of reproductive interventions, while also delving into the underlying mechanistic pathways linking endometriosis with inflammatory processes.